Análise probabilística de incompatibilidade entre a qualidade da água de rios do estado do Espírito Santo e os padrões de enquadramento legal - Guimarães, Brunna Oliveira (2013)
The main objective of this research was the construction and analysis of probabilistic curves of water quality incompatibility of rivers in the state of Espírito Santo and environmental quality standards, viewing the implementation of frameworkasa water resource management tool.The choice of water courses to conduct the present study was based on the availabilityand extension of water-quality data historical series provided by the Moacir Carvalheira de Mendonça Analyses and Environmental Parameters Laboratory, from the Environmentaland Water Resources State Institute.Therefore, the hydrographic basins of the rivers Jucu, Reis Magos, Santa Maria da Vitória and the areaof Rio Doce River pertaining to the state of Espírito Santo were chosen. To discuss the possibilities of framework probabilistic curves of incompatibility to pH parameters, dissolved oxygen, turbidity, total solids, oxygen biochemical demands, total phosphorus andthermotolerant coliforms were used.Considering the monitoring recordsavailable, the results indicated that adoptingdifferentiated frameworksfrom upstream to downstream for the water bodies examined is inadequate. Additionally, hydrological seasonality is relevant tovariations of concentration associated with turbidity, when eventual attempts to classify water courses in class 1 are considered.Any frameworkadopted for the basinsexamined will require relevant efforts to reduce total phosphorus and thermotolerant coliforms concentrations in the planning activities established by the basin plans.